An Improved Equivalent Circuit Simulation of High Frequency Ultrasound Transducer - Shen, Zhitian; Xu, Jie; Li, Zhangjian; Chen, Youwei; Cui, Yaoyao; Jian, Xiaohua (Frontiers in Materials, 2021)
The equivalent circuit simulation plays an important role in the design of ultrasound transducer. However, the existing methods are difficult to achieve the effect of matching and backing layer, and not able to accurately simulate the transducer with cable. Especially in the application of high frequency ultrasound, the long cable has a great influence on the performance of the transducer. To overcome these limitations, this paper proposed an improved equivalent circuit method, which combined Leach model and transmission line model. It can realize the complete simulation of ultrasound transducer with a long cable, matching layer, and backing layer in PSPICE circuit simulation software when the parameters were measured. Its principles were briefly introduced, and ultrasound transducers with different frequencies (12 and 20 MHz), different matching layers, and different cable lengths (0.5-2.5 M) were designed and fabricated to verify the effectiveness of the method, which is also compared with the traditional KLM method using PiezoCAD. The experiment results showed that the long cable, matching layer, and backing layer have a significant impact on the performance of high frequency ultrasound transducers, and this proposed method has good agreement with these results. Moreover, for the simulation of the complete transducer, the effect of this method is better than KLM model. Besides, this method does not need to know the specific equivalent circuit of matching, backing layer, or cable wire, it can accurately predict the impedance and phase of the transducer through the material parameters, which is very helpful for the material selection and optimization of subsequent transducer design and fabrication. The study indicates that this improved equivalent circuit method is suitable to be applied in the general circuit simulation software and provides strong support for the high frequency transducer and system design.